News uncertianty in Brexit UK - Renato Faccini; Edoardo Palombo (Danmarks Nationalbank, 2020)
After the Brexit referendum the behavior of the UK economy defied widespread expectations, as it did not exhibit a V-shaped recession, but a slow decline in production. We show that this pattern of propagation arises when uncertainty is about future, rather than current fundamentals, and if the expected duration of uncertainty is sufficiently long. We reach this conclusion within the confines of a heterogeneous firms model featuring news uncertainty, instead of conventional uncertainty shocks. In the quantitative analysis, uncertainty is informed by firm-level probability distributions on the expected effect of Brexit on sales.
Keywords: E22; E32; E65; O40; 330; Recent economic and monetary trends; Productivity and competitiveness